Gambaran Histopatologi Ginjal Mencit (Mus musculus Balb/C) yang Diinfeksi dengan Plasmodium berghei - Miftah Ar Rahmah; Adrial Adrial; Yenita Yenita (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: P. berghei is a parasite that causes malaria in small rodents. This parasite is analogous to P. falciparum which causes severe malaria in humans with the highest risk of death compared to 4 other plasmodium species. Complications of falciparum malaria in renal microcirculation is AKI (Acute Kidney Injury). AKI is preceded by the incidence of ATN (Acute Tubular Necrosis) and MPGN (Mesangioproliferative Glomerulonephritis) with ATN being the highest prevalence. Objective: This study aims to determine the histopathological appearance of renal tubules of white mice Mus musculus Balb/C which are infected with P. berghei. Methods: Descriptive analysis method with quantitative approach is used in this study. The study was conducted at the Anatomical Pathology Laboratory of the Faculty of Medicine, Andalas University. The study was conducted since February to October 2020. The sample size was determined by the Federer formula (2008). Results: Percentage of renal tubular cell damage which were 8.42% for the control group, 4.52% for the pellet extract group, and 2.74% for supernatant extract group. Conclusion: The study concluded that highest percentage of kidney tubular cell damage was found in the kidney of mice immunization with the control group, and the lowest percentage of kidney tubular cell damage was found in the kidney of mice immunization with supernatant extract.